Perjalanan Ilmu Kaligrafi Dalam Lintasan Sejarah - Putri Wulandari (Yayasan Haiah Nusratul Islam, 2024)
Calligraphy is a scientific discipline regarding artistic writing which contains the value of beauty and in writing it must pay attention to predetermined writing rules such as single letters, their layout, ways of writing and the meaning represented in the writing. Khat has a complex and interesting historical background from its emergence on the Arabian Peninsula to its development throughout the world and even into the archipelago. The aim of the research is to more concretely understand the history of khat's journey. The research applies the Systematic Literature Review (SLR) method through the use of Publish or Perish (PoP) as a data searcher and then the VosViewers application is used to review it. The research produced findings that the idea of ​​the history of khat's journey can expand the knowledge of various aspects of the emergence and development of khat, as well as foster critical, innovative and quality thinking patterns in a learning perspective.